Management of shoulder pain by UK general practitioners (GPs): a national survey. Issue 6 (21st June 2017) - Artus, Majid; van der Windt, Danielle A; Afolabi, Ebenezer K; Buchbinder, Rachelle; Chesterton, Linda S; Hall, Alison; Roddy, Edward; Foster, Nadine E
Abstract : Objectives: Studies in Canada, the USA and Australia suggested low confidence among general practitioners (GPs) in diagnosing and managing shoulder pain, with frequent use of investigations. There are no comparable studies in the UK; our objective was to describe the diagnosis and management of shoulder pain by GPs in the UK. Methods: A national survey of a random sample of 5000 UK GPs collected data on shoulder pain diagnosis and management using two clinical vignettes that described primary care presentations with rotator cuff tendinopathy (RCT) and adhesive capsulitis (AdhC). Results: Seven hundred and fourteen (14.7%) responses were received. 56% and 83% of GPs were confident in their diagnosis of RCT and AdhC, respectively, and a wide range of investigations and management options were reported. For the RCT presentation, plain radiographs of the shoulder were most common (60%), followed by blood tests (42%) and ultrasound scans (USS) (38%). 19% of those who recommended a radiograph and 76% of those who recommended a USS did so 'to confirm the diagnosis'. For the AdhC presentation, the most common investigations were blood tests (60%), plain shoulder radiographs (58%) and USS (31%). More than two-thirds of those recommending a USS did so 'to confirm the diagnosis'. The most commonly recommended treatment for both presentations was physiotherapy (RCT 77%, AdhC 71%) followed by non-steroidal anti-inflammatory drugs (RCT 58%, AdhC 74%). 17% opted to refer the RCT to secondary care (most often musculoskeletal interface service), compared with 31% for the AdhC. Conclusions: This survey of GPs in the UK highlights reliance on radiographs and blood tests in the management of common shoulder pain presentations. GPs report referring more than 7 out of 10 patients with RCT and AdhC to physiotherapists. These findings need to be viewed in the context of low response to the survey and, therefore, potential non-response bias.